Aberrant regional homogeneity in Parkinson's disease: A voxel-wise meta-analysis of resting-state functional magnetic resonance imaging studies. (January 2017) - Pan, PingLei; Zhan, Hui; Xia, MingXu; Zhang, Yang; Guan, DeNing; Xu, Yun
Highlights: Regions of both increased and decreased ReHo are observed in PD. Altered ReHo is consistently observed in the default mode and motor networks in PD. Impairment and compensation of intrinsic brain activity coexist in PD. Abstract: Studies of abnormal regional homogeneity (ReHo) in Parkinson's disease (PD) have reported inconsistent results. Therefore, we conducted a meta-analysis using the Seed-based d Mapping software package to identify the most consistent and replicable findings. A systematic literature search was performed to identify eligible whole-brain resting-state functional magnetic resonance imaging studies that had measured differences in ReHo between patients with PD and healthy controls between January 2000 and June 4, 2016. A total of ten studies reporting 11 comparisons (212 patients; 182 controls) were included. Increased ReHo was consistently identified in the bilateral inferior parietal lobules, bilateral medial prefrontal cortices, and left cerebellum of patients with PD when compared to healthy controls, while decreased ReHo was observed in the right putamen, right precentral gyrus, and left lingual gyrus. The results of the current meta-analysis demonstrate a consistent and coexistent pattern of impairment and compensation of intrinsic brain activity that predominantly involves the default mode and motor networks, which may advance our understanding of the pathophysiological mechanisms underlying PD.